2013
DOI: 10.1002/humu.22396
|View full text |Cite
|
Sign up to set email alerts
|

Ferroportin Diseases: Functional Studies, a Link Between Genetic and Clinical Phenotype

Abstract: Ferroportin (FPN) mediates iron export from cells and this function is modulated by serum hepcidin. Mutations in the FPN gene (SLC40A1) lead to autosomal dominant iron overload diseases related either to loss or to gain of function, and usually characterized by normal or low transferrin saturation versus elevated transferrin saturation, respectively. However, for the same mutation, the phenotypic expression may vary from one patient to another. Using in vitro overexpression of wild-type or mutant FPN proteins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 35 publications
3
35
0
Order By: Relevance
“…The expression of Fpn-WT resulted in a reduction of ;67% in intracellular ferritin concentrations compared with the control cells. As expected from previous reports (27)(28)(29)(30), cells expressing LOF mutants, G80S, R88G, D157G, D157Y, or V162D were iron loaded, whereas the cells expressing GOF mutants N144H, N144T, C326S, or S338R were iron depleted, similar to those expressing Fpn-WT.…”
Section: Impact Of Ferroportin Disease Mutations On Intracellular Fersupporting
confidence: 88%
See 2 more Smart Citations
“…The expression of Fpn-WT resulted in a reduction of ;67% in intracellular ferritin concentrations compared with the control cells. As expected from previous reports (27)(28)(29)(30), cells expressing LOF mutants, G80S, R88G, D157G, D157Y, or V162D were iron loaded, whereas the cells expressing GOF mutants N144H, N144T, C326S, or S338R were iron depleted, similar to those expressing Fpn-WT.…”
Section: Impact Of Ferroportin Disease Mutations On Intracellular Fersupporting
confidence: 88%
“…Studies have shown that the LOF mutations, which lead patients to exhibit the classic phenotype of Kupffer cell iron accumulation, affect the localization of Fpn on the cell surface. Consistently, several studies reported intracellular localization of the G80S, R88G, D157G, D157Y, and V162D Fpn mutants (28)(29)(30)(31)42). However, other studies found localization of G80S (43), R88G (29), D157G, and V162D (44), primarily at the cell surface.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…53 Adult onset non-HFE-HH forms (HH types III and IV) are either caused by mutations in TFR2 encoding transferrin receptor 2, 16 or the hepcidin receptor ferroportin ( FPN/SLC40A1 ), generally referred to as HH type IV. 55 Gain-of-function mutations within ferroportin confer resistance to hepcidin binding and thus prevent ferroportin internalization and degradation (HH type IV, classical ferroportin disease with gain-of-function mutation). As a consequence, uncontrolled iron export from cell types expressing ferroportin, such as duodenal enterocytes or macrophages, causes high levels of iron overload.…”
Section: Introductionmentioning
confidence: 99%
“…In HH type 4 (OMIM #606069) patients have loss‐ or gain‐of‐function mutations in the iron exporter ferroportin that is encoded by the SLC40A1 gene (OMIM *604653; Detivaud et al. ). HH type 3 (OMIM #604250) is a rare form of HH characterized by genetic alterations in the Transferrin receptor 2 ( TFR2 ) gene (OMIM *604720; Camaschella et al.…”
Section: Introductionmentioning
confidence: 99%